Can agroecological living landscapes (ALLs) solve food, land and water system challenges? - Malaiappan, Sudharsan; Renduchintala, S.; Sikka, Alok (International Water Management Institute, 2023)
Globally Food, Land, and Water Systems (FLWS) are being degraded rapidly. Indian agriculture is heavily dependent on natural resources. Agriculture plays a significant role in India’s $3.5 trillion economy, employing 43% of the available labor force. The share of agriculture and allied sectors in total gross value added (GVA) of the economy is 18.8% during 2021-22.